2012
DOI: 10.1007/s00417-012-2033-5
|View full text |Cite
|
Sign up to set email alerts
|

Foveal light exposure is increased at the time of removal of silicone oil with the potential for phototoxicity

Abstract: Foveal light exposure, and therefore the potential for phototoxicity, is transiently increased at the time of removal of silicone oil. This is due to uneven macular illumination resulting from the optical vignetting effect of different silicone oil bubble sizes. The increase in foveal light exposure may be significant when the procedure is performed under bright operating microscope light on already stressed photoreceptors of an eye filled with silicon oil. We advocate the use of precautions, such as central s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 19 publications
1
19
1
1
Order By: Relevance
“…Enhanced phototoxicity, especially at the time of silicone oil removal, is a different discussed mechanism of vision loss [34]. Since all of our patients experience vision loss before oil removal, we do not support this theory.…”
Section: Pathophysiologymentioning
confidence: 55%
“…Enhanced phototoxicity, especially at the time of silicone oil removal, is a different discussed mechanism of vision loss [34]. Since all of our patients experience vision loss before oil removal, we do not support this theory.…”
Section: Pathophysiologymentioning
confidence: 55%
“…The incidence of this phenomenon has been reported to be anywhere from 1–30% [18, 2931]. In the largest series to date, Moya and collaborators [21] found that 14 of 421 (3.3%) eyes that underwent silicone oil removal developed un-explained visual loss.…”
Section: Discussionmentioning
confidence: 99%
“…Several hypotheses have been proposed including sudden changes in potassium concentration in retro-oil fluid that may lead to macular dysfunction due to photoreceptor apoptosis on oil removal, 18,20 photo-toxicity at the time of silicone oil removal, 15,21,22 and fibrogenic growth factor disturbances. 23 Of the 14 patients who had at least two SL reduction in visual acuity in our study this appeared to happen at the time of oil removal.…”
Section: Discussionmentioning
confidence: 99%